IMMUNOPATHOGENESIS OF ACUTE RESPIRATORY INFECTIONS AND TACTICS OF RATIONAL CHOICE OF ETIOTROPIC IMMUNOMODULATORY THERAPIES IN CHILDREN - V. V. Malinovskaya; V. P. Timina; L. N. Mazankova; T. A. Chebotareva (LLC "Diagnostics and Vaccines", 2015)
The article demonstrates that the basis for pathogenesis of acute respiratory infection (ARI ) is a deficiency in a number of factors of virus protection. This deficiency manifests itself through low concentration of interferon and secretory IgA in the nasal mucosa at higher levels of IL-8, alongside with low serum antiviral activity and significant inhibition of interferon production and reduction of the compensatory mechanisms of adaptive immunity. These disorders require prescription of alpha-interferon preparations. For infants and children with a burdened pre-morbid background, regardless of age, such preparations can be administered with all clinical forms of ARI; in older children - with severe forms, including complications. Alpha-interferon preparations can be introduced at in any stage of the disease. Combination therapy with alpha-interferon drugs (VIFERON® suppositories and VIFERON® ointment) allows for enhanced clinical and immunological effects of therapy.